Complexity theory and action research: na epistemological research framework (Research, Society and Development, 2020)
This article aims to reflect on the construction of scientific knowledge from the perspective of complexity from action-research. A paradigm shift in scientific practice includes uncertainties and risks, a Science made, "ready to last" is different from "Science in action", one that does not define any research process and according to the social context. It is a theoretical essay, book reviews, journal articles available on the internet, as well as advanced reflections of the experience of the authors' field. Finally, we highlight the relevance of an epistemological framework capable of articulating theory and practice, religious research and action to obtain a better understanding of the history of an end of explanation, reflected and it intervenes in the middle of a research epistemology. This reflection allowed us to think of action research as an epistemological research path where the main aspects differ from classical research and value the construction of knowledge, from a participatory and collective approach.